2022
DOI: 10.3390/ijms232314627
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Plant Oxylipins

Abstract: For immobile plants, the main means of protection against adverse environmental factors is the biosynthesis of various secondary (specialized) metabolites. The extreme diversity and high biological activity of these metabolites determine the researchers’ interest in plants as a source of therapeutic agents. Oxylipins, oxygenated derivatives of fatty acids, are particularly promising in this regard. Plant oxylipins, which are characterized by a diversity of chemical structures, can exert protective and therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 256 publications
0
10
0
Order By: Relevance
“…A few studies indicated that plant oxylipins showed anticancer, antitumor, antifungal, anti-inflammatory and immunomodulatory effects. 41 In this study, the key targets, such as PIK3CA, AKT1 and ESR1, were associated with multiple oxylipins. There are 10 oxylipins acting on the ESR1 target, 9 oxylipins acting on the AKT1 target and 6 oxylipins acting on the PIK3CA target.…”
Section: Biosynthetic Pathway Of Steroidal Saponins and Flavonoids In...mentioning
confidence: 72%
“…A few studies indicated that plant oxylipins showed anticancer, antitumor, antifungal, anti-inflammatory and immunomodulatory effects. 41 In this study, the key targets, such as PIK3CA, AKT1 and ESR1, were associated with multiple oxylipins. There are 10 oxylipins acting on the ESR1 target, 9 oxylipins acting on the AKT1 target and 6 oxylipins acting on the PIK3CA target.…”
Section: Biosynthetic Pathway Of Steroidal Saponins and Flavonoids In...mentioning
confidence: 72%
“…A bioactivity-guided approach led to the isolation of three main constituents from the extract with potential cytotoxic effects on cells, namely pinellic acid (PA), traumatic acid (TA), and 9,10-dihydroxy-8-oxsooctadec-12-enic acid (MUA). The compounds belong to oxylipin family, which are products from the oxygenation of fatty acids accumulated in plants in response to stress conditions [ 20 , 21 ]. They exhibit interesting biological activities, including pro-/anti-inflammatory, antimicrobial, neuroprotective, and regulatory effects [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…TA is an oxylipin biosynthesized in plants by non‐enzymatic oxidation of traumatin (12‐oxo‐trans‐10‐dodecanoic acid) 29 . Plant oxylipins, characterized by diverse chemical structures, are an important class of secondary metabolites that protect plants from adverse environmental factors and can exert protective and therapeutic effects in animal cells 30 . Hence, as a member of the oxylipins, TA is an essential medium of dialogue between plants and animals.…”
Section: Discussionmentioning
confidence: 99%
“…29 Plant oxylipins, characterized by diverse chemical structures, are an important class of secondary metabolites that protect plants from adverse environmental factors and can exert protective and therapeutic effects in animal cells. 30 Hence, as a member of the oxylipins, TA is an essential medium of dialogue between plants and animals. Furthermore, TA has recently been detected in the peripheral blood of sarcopenia subjects 31 and patients with inflammatory bowel disease, 32 illustrating that TA is also an endogenous metabolite.…”
Section: Discussionmentioning
confidence: 99%